Strategi Public Relation dalam Mengembangkan Citra Lembaga Madrasah di MAN 2 Ponorogo - Ririn Nuraini; Sri Ambarwati Cahyaningrum (Southeast Asian Journal of Islamic Education Management, 2022)
Abstract   This study aims to explain Public Relations in developing the Image of Madrasah Institutions at MAN 2 Ponorogo. To explain the implementation of the Public Relations strategy in developing the image of Madrasah Institutions at MAN 2 Ponorogo. This research uses a qualitative approach and the type of research is a case study. The results of the analysis show: Public relations at MAN 2 Ponorogo include providing information services from an agency/educational institution to customers (the wider community) and prioritizing good communication. In MAN 2 Ponorogo, there are two types of communication commonly used, namely verbal communication and nonverbal communication. The pattern of public relations strategy at MAN 2 Ponorogo includes four main steps, namely planning by identifying problems and planning programs based on problem analysis, organizing by forming administrators and delegation of authority who will be involved in programs of public relations activities, implementation of program implementation and communication with strategy. and program reporting/evaluation. Implementation of public relations strategy through internal and external activities. By using school strategies, functional, operational. This public relations strategy has a great contribution to the image of the institution at MAN 2 Ponorogo.   Keywords: Public Relations Strategy; Image of Madrasah Institutions